Exposure to 1800 MHz GSM- like radiofrequency electromagnetic field reduces follicular development and overall fertility of female rats - Ali S. H. Alchalabi; Erkihun Aklilu; Abd Rahman Aziz; S. H. Ronald; Mohd Azam Khan Goriman Khan (2015)
In the current study, the effect of 1800 MHz radiofrequency radiation exposure on female rats’ fertility was investigated. The study was conducted on the nine groups of female Sprague-Dawley rats (20 rats/group) with a control group and exposure groups which exposed to EMF 1hr/day and 2hr/day for 15, 30 and 60 days respectively. Animals were whole-body exposed using a GSM-like radiofrequency generator at SAR level 0.048 W/Kg. After the last exposure, rats were divided into two subgroups for fertility evaluation, ovari-an follicle count, and oxidative stress assessment. Prolonged cohabitation day until delivery in exposure groups animals compared to control was ob-served. Moreover, a significant decrease in the number of pups per delivery was observed. Ovarian follicle count showed a dramatic decrease in exposure groups throughout the experiment except the number of atretic follicles was significantly increased compared to control groups. FSH level was signifi-cantly reduced within exposure groups. LH level remained constant except in 2hr. /day group for 60 days. Melatonin levels were significantly lower in ex-posure groups. Glutathione peroxidase activity was reduced in most exposure groups. Malondialdehyde levels were raised significantly in most expo-sure groups compared to the control. Our findings conclude that exposure to electromagnetic field's cause female reproductive activity impairment.